Public responsibility in the matter of gender violence (Special reference to the daughters and sons of battered mothers) - Peral López, María del Carmen (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2020)
Abstract.The daughters and children of women victims of gender violence suffer a double victimization, having lived in an environment of permanent violence directed in principle towards their mothers, and can be triple when they witness this type of violence, which even reaches cause them death. After the cessation of the cohabitation of the couple they do not stop suffering, in many cases, they begin a regime of visits with the father, situation that exposes them to a new type of violence towards them or to the mother through them and they, the called vicarious violence. In spite of the reforms of 2015, the visitation, stay and communication to parents that violate mistreatment of the mother continue to be granted, and practically no measures have been taken to protect minors in these cases in the three years since entry. in force of said reforms. While the desired training of legal operators leaves its mark, it is necessary to apply measures to protect minors and go a step further by becoming aware of the damage that is being committed, assuming the responsibility that corresponds to the State and articulating compensation measures as in his day was with the victims of terrorism. Surprisingly, neither Organic Law 1/2004, nor the regional legislations have included definitions of institutional violence, violence that entails the obligation to repair the damage by the State and its translation in compensation for the victimsKeywords: violence, gender, institutional, responsibility, Administration, minors.